2010
DOI: 10.1002/pmic.200900484
|View full text |Cite
|
Sign up to set email alerts
|

Acute metal stress in Populus tremula×P. alba (717‐1B4 genotype): Leaf and cambial proteome changes induced by cadmium2+

Abstract: The comprehension of metal homeostasis in plants requires the identification of molecular markers linked to stress tolerance. Proteomic changes in leaves and cambial zone of Populus tremula x P. alba (717-1B4 genotype) were analyzed after 61 days of exposure to cadmium (Cd) 360 mg/kg soil dry weight in pot-soil cultures. The treatment led to an acute Cd stress with a reduction of growth and photosynthesis. Cd stress induced changes in the display of 120 spots for leaf tissue and 153 spots for the cambial zone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 69 publications
4
38
1
Order By: Relevance
“…Durand et al (2010) observed a similar effect in poplar leaves upon Cd administration to intact plants for longer times of exposure. Authors hypothesized that alpha-tubulin decrease could reflect the negative impact of long term metal stress on the growth of leaves.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Durand et al (2010) observed a similar effect in poplar leaves upon Cd administration to intact plants for longer times of exposure. Authors hypothesized that alpha-tubulin decrease could reflect the negative impact of long term metal stress on the growth of leaves.…”
Section: Discussionsupporting
confidence: 65%
“…Cd content was measured as reported by Durand et al (2010) on digested leaves samples including petioles. In detail, dried material was milled to a fine powder (Grinder, IKA, Staufen, Germany) and then mineralized.…”
Section: Measure Of CD Concentrationmentioning
confidence: 99%
“…Peroxiredoxin is a thiol-specific peroxidase that detoxifies peroxides and also plays essential roles in enzyme activation and redox sensing [51,52]. The up-regulation of peroxiredoxin has been reported in Cd-challenged Populus [17] and rice [22]. Here, in Cd-stressed soybean plants without BABA pre-treatment, a higher abundance of antioxidant enzymes was not detected.…”
Section: Discussioncontrasting
confidence: 62%
“…For example, a relatively low abundance of proteins involved in the photosynthetic electron transport chain and Calvin cycle has been reported in Cd-exposed poplar [18,19], Populus [17], and Thlaspi [57]. Our present proteomic analysis of soybean leaf proteins revealed high abundance of oxygen-evolving enhancer protein 1 and ribulose bisphosphate carboxylase small chain 1 in both nonprimed and BABA-primed leaves.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation